Efficacy of Metarhizium anisopliae to control Aeneolamia varia (Hemiptera: Cercopidae), in a sugar cane - MATABANCHOY-SOLARTE, JESÚS ARVEY; BUSTILLO PARDEY, ALEX ENRIQUE; CASTRO-VALDERRAMA, ULISES; MESA-COBO, NORA CRISTINA; MORENO-GIL, CARLOS ARTURO (Revista Colombiana de Entomología, 2012)
In June 2007, the spittlebug Aeneolamia varia (Hemiptera: Cercopidae) was found in sugar cane crops located in the rural zone of the municipality of Yotoco, Cauca Valley, Colombia. This insect is considered an important pest of pastures and a potential pest of sugar cane crops. Due to this situation, we planned to evaluate, under field conditions, in a sugar cane field, different strains of Metarhizium anisopliae (CCMa0906, CCMa1008, CoMa01 and CeMa9236), selected in previous studies. A first experiment was conducted in a cane field to select the strain with greatest efficacy at the dose of 1.0 x 1013  conidia/ha on nymphs of A. varia. Then, in two other field experiments, the selected strain (CeMa9236) was evaluated when applied at different dosages (1 x 1012, 5 x 1012, 1 x 1013, 5 x 1013  conidia/ha). It was found that mortality increased with dosage. At 5 x 1013  conidia/ha, the greatest mortality was found in the two experiments (66% and 72%), however, for purposes of control in commercial sugar cane plots infested with A. varia, lower dosages (5 x 1012 to 1 x 1013 conidia/ha) should be tested.